Electrosorption of Hexavalent Chromium Ions by MnO2/Carbon Fiber Composite Electrode: Analysis and Optimization of the Process by Box-Behnken Design - M. Issa, Zainab; H. Salman, Rasha; Basavaraj Bhagawati, Prashant (Iraqi Journal of Chemical and Petroleum Engineering, 2023)
A nano manganese dioxide (MnO2) was electrodeposited galvanostatically onto a carbon fiber (CF) surface using the simple method of anodic electrodeposition. The composite electrode was characterized by field emission scanning electron microscopy (FESEM), and X-ray diffraction (XRD). Very few studies investigated the efficiency of this electrode for heavy metals removal, especially chromium. The electrosorption properties of the nano MnO2/CF electrode were examined by removing Cr(VI) ions from aqueous solutions. NaCl concentration, pH, and cell voltage were studied and optimized using the Box-Behnken design (BDD) to investigate their effects and interactions on the electrosorption process. The results showed that the optimal conditions for the removal of Cr(VI) ions were a cell voltage of 4.6 V, pH of 2 and NaCl concentration of 1.5 g/L. This work indicated that MnO2/CF electrode was highly effective in removing Cr(VI) ions and the BBD approach was a feasible and functional method for evaluating the experimental data.